2019
DOI: 10.1111/odi.13155
|View full text |Cite
|
Sign up to set email alerts
|

Oral keratosis of unknown significance shares genomic overlap with oral dysplasia

Abstract: Objectives To identify molecular characteristics of keratosis of unknown significance and to nominate pathways of molecular progression to oral cancer. Our work could provide a rationale for monitoring and treating these lesions definitively. Methods Patients with oral leukoplakia were eligible for our prospective observational study. We correlated alterations in cancer‐associated genes with clinical and histopathologic variables (keratosis of unknown significance vs. moderate‐to‐severe dysplasia) and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 41 publications
3
33
2
Order By: Relevance
“…It is worth mentioning that 27.8% of cases with no dysplasia, referred as keratosis of unknown significance (KUS), developed into OSCC in our study (Woo, Grammer, & Lerman, 2014). Recent studies have revealed that KUS and dysplasia share similar molecular and genomic characteristics (Villa et al., 2019). KUS is not as benign as was thought historically; it might be a very early form of dysplasia and correspond to the “first strike” of the “three strikes” in multistep carcinogenesis (Villa et al., 2019; Vogelstein & Kinzler, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that 27.8% of cases with no dysplasia, referred as keratosis of unknown significance (KUS), developed into OSCC in our study (Woo, Grammer, & Lerman, 2014). Recent studies have revealed that KUS and dysplasia share similar molecular and genomic characteristics (Villa et al., 2019). KUS is not as benign as was thought historically; it might be a very early form of dysplasia and correspond to the “first strike” of the “three strikes” in multistep carcinogenesis (Villa et al., 2019; Vogelstein & Kinzler, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that KUS and dysplasia share similar molecular and genomic characteristics (Villa et al., 2019). KUS is not as benign as was thought historically; it might be a very early form of dysplasia and correspond to the “first strike” of the “three strikes” in multistep carcinogenesis (Villa et al., 2019; Vogelstein & Kinzler, 2015). Therefore, all OLK lesions should be followed by observation at close intervals (3–6 months) independent of the presence or absence of dysplasia, emphasizing the need for periodic biopsies and tools for detecting malignant transformation in suspicious lesions (Holmstrup, Vedtofte, Reibel, & Stoltze, 2007; Woo, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A total of nine patients (9/20; 45%) developed OSCC (5 patients with moderate‐to‐severe dysplasia and 4 with KUS). Five of these same nine patients were from the PVL group (5/6; 83.3%), while the other four were from the conventional OLK group (4/14; 28.5%; Villa, Hanna, et al, 2019). One interpretation is that KUS in this study correlates with the “genotypic” dysplasia intermediate cluster defined by Farah and Fox (Farah & Fox, 2019).…”
Section: Molecular Profile Of Oral Leukoplakiamentioning
confidence: 95%
“…More recently, a pattern of discrete segregation was seen in another study which showed that oral keratosis of unknown significance (KUS) shared genomic overlap with oral epithelial dysplasia (Villa, Hanna, et al, 2019). The authors used a targeted next‐generation sequencing approach of 447 genes of interest in cancer in lieu of whole exome sequencing and showed that alterations in KMT2C and TP53 were most frequent (75% and 35%, respectively) in both KUS and OED (Villa, Hanna, et al, 2019). A total of nine patients (9/20; 45%) developed OSCC (5 patients with moderate‐to‐severe dysplasia and 4 with KUS).…”
Section: Molecular Profile Of Oral Leukoplakiamentioning
confidence: 99%
“…A subset of OL presenting with “genotypic dysplasia” lacking histopathological evidence of “phenotypic dysplasia” was first identified by Farah et al (2019) in a study exploring transcriptomic differences between dysplastic and non‐dysplastic OL (Farah & Fox, 2019). Additionally, leukoplakia without dysplasia (termed keratosis of unknown significance [KUS] by some authors) has been shown to share genomic features with dysplastic OLs (Villa, Hanna, et al, 2019). Collectively, these studies support the notion that some leukoplakias may be precancerous regardless of whether dysplasia is present on biopsy.…”
Section: Introductionmentioning
confidence: 99%